Energy Development Index (EDI) dan Implikasinya terhadap Kemiskinan di Indonesia: Studi Pendekatan Persamaan Simultan - Dewi, Ni Made Wulan Puspita (Politeknik Statistika STIS, 2025)
This study analyzes the reciprocal relationship between energy development and poverty in Indonesia using the Two Stage Least Squares (2SLS) approach, based on 2023 data from 34 provinces. EDI includes the share of energy expenditure, electricity consumption per capita, access to electricity, and access to clean cooking fuels. The results indicate that declining poverty rates and increased FDI-to-GRDP ratios significantly enhance EDI. In turn, higher EDI scores raise junior secondary Net Enrollment Rates and life expectancy at birth, although only life expectancy contributes to poverty reduction. Conversely, income inequality, measured by the gini ratio, intensifies poverty, while a greater number of health workers improves life expectancy at birth. Policy simulations suggest that reducing the gini ratio to 0,30 could lower the poverty rate by up to 7,848%. These findings underscore the importance of inclusive energy development and reduced income inequality as key elements in poverty alleviation strategies.